Uso de enzimas proteasas en la alimentación de pollos de engorde. - Gavilanez Olvera, Madelaine Karen (2019)
SUMARY Enzymes are amino acid polymers that direct catalytic activity in various biological systems, thanks to the ability of chemical accelerations. The enzyme that hydrolyzes phytic phosphorus (or phytate) is called phytase. The objective of the research was to generate published information on the use of protease enzymes in broiler chickens. This documentary research work was developed based on the collection, sequence and review of articles, executed on protease enzymes, on issues related to the feeding of broiler chickens, especially on the proper use of enzymes. The information was collected between March and April of 2019. The methods used were based on response analysis, which made it possible to obtain results from written works and online publications. On the other hand, bibliographic and documentary research have shown the benefits of productive behavior, since they also act on non-starch polysaccharides (PNA) in diets based on barley and wheat. Thus increasing the nutritional quality of the feed acting as a supplementary source of energy and fats and oils. Diets with DDGS have a better performance in chickens fed with 25% DDGS weighing 1096 grams in the growth phase. The inclusion of 25% of DDGS and the 10% reduction in protein, amino acids and energy did not show any effect on bird performance. The use of a protease not only contributes to increasing the profitability of a broiler producer, but also has a positive impact on the environment, helping to improve the quality of the litter and the associated associated parameters of well-being, of great economic importance. Key words: Enzymes, proteases, broiler chickens and productive parameters